Study on composition of essential oil extraction from lemongrass using supercritical carbon dioxide - Phuong Ha, Huynh Ky (Animo Repository, 2005)
The Supercritical Fluid Extraction (SCFE) is a new technique to get pure and highly quality essential oils from natural plants. In this study, the apparatus system of SCFE using Carbon Dioxide has been set-up to extract the essential oils from Lemongrass (leaves and stems). The volume of the extractor is 500 ml. The extraction temperature is varied from 35oC to 50oC while the pressure is from 90atm to 110atm. The flow rate applied for extraction is 0.5m3/hr. Compositions of essential oil are determined by using GC-MS data and the changing of light components content (mycrene and limonene) depend on extraction conditions will be observed. The different of essential oil compositions from Supercritical Extraction and Steam distillation extraction are identified and compared to pure essential oil from U.K. The drying schemes (heat and air) will be investigated based on GC data.